#TITLE_ALTERNATIVE# - HASOLOAN SITUMORANG (NIM 121 04 063), ANDREW
The application of strain gauge in determining strain value at one particular example of test to own the accuracy which is better than the application of dial gauge. But the application of strain gauge can only just used once so that costlier relative to use it. The application of measurement plate makes the application of strain gauge can be used multiply. This measurement plate can be used to determine the axial strain in UCS test. But before the measurement plate can be aplicated to determining axial strain, it must have to being calibrated. So that the relation between strain of the measurement plate and the sample's strain can be determined. The determination of relation between measurement plate's strain and the strain of sample has been conducted at axial direction. And then, the axial strain that happened at measurement plate by using strain gauge is calibrated to sample's axial strain. So that obtained a curve calibrate between strain of dial gauge with the strain of strain gauge at same encumbering condition. The result of curve calibrate obtained by pursuant to examination is : Test Calibrate equation I y1 = 29,09x - 6E-07 II y2 = 29,9x - 1E-05 III y3 = 31,6x - 1E-05 IV y4 = 31,5x - 1E-05 V y5 = 31,6x - 1E-05 VI y6 = 33,4x - 6E-05 VII y7 = 31.4x + 3E-06 VIII Y8 = 32.8x - 6E-06 Where : x = dial gauge's strain y = strain gauge's strain Keywords : dial gauge, strain gauge, calibration.